Polish Precursors of United Europe - Smyk, Grzegorz (Great Theorists of Central European Integration, 2023)
The idea of a supra-state and transnational political unions in Europe has been present in Polish political thought since the beginning of modern times. It became the foundation for the creation of a common Polish-Lithuanian state in 1569 – the Polish-Lithuanian Commonwealth, based on the principle of voluntary political union, equality of the constituent states, and respect for national differences and religious tolerance. Despite the fall of the Polish-Lithuanian Commonwealth at the end of the 18th century, these ideas were adapted to the political programmes of Polish representatives of European political thought in the 19th and early 20th centuries. Even at the beginning of the 19th century, visionaries such as Prince Adam Jerzy Czartoryski proposed a supranational and pan-European agreement between superpowers and smaller European states, based on the principles of equality, political balance, peaceful coexistence and cooperation, as well as respect for national aspirations. Others, such as Walerian Krasiński or Franciszek Smolka, linked their hopes for a new, just European order and the preservation of Polish national identity with the idea of autonomy within the Slavic community (pan-Slavism) or the multinational Austro-Hungarian Monarchy. The visions of a united Europe remained alive in the Polish political doctrine of the interwar period. The traditions of the multicultural pre-partition Republic of Poland constituted the basis for the federal concepts offered to its former nations, on the grounds of equality and respect for their separateness (the Jagiellonian idea). In the views of political thinkers such as Witold Kamieniecki or Stefan Gużkowski, the Republic of Poland shaped in this way, was to serve as a bridge connecting the European nations in their opposition of German or Soviet expansion, and to build mutual relations between states based on common political and economic interests (Intermarium, Three Seas). The distinguishing features of the views of the Polish precursors of the idea of a united Europe were the beliefs that, in international relations, it is possible to reconcile national egoism with the desire to build supranational and pan-European structures, and that European nations, treated equally, are able to develop universally accepted principles of cooperation and peaceful coexistence. KEYWORDS: Federalism, Panslawism, Jagiellonian Idea, Intermarium, Threseas